DINAMIKA KONFLIK DALAM PEMILIHAN KEPALA DESA PANDAU JAYA TAHUN 2017 - Irawan, Aldo; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research is motivated by the simultaneous head election held for the first time in Pandau Jaya Village, Siak Hulu District, Kampar Regency. The Village Head Election held in Pandau Jaya Village aims to elect the Village Chief from 2017-2022. Election of Village Head is also a form of democracy in Pandau Jaya Village. The procedure for organizing the election of the Village Head in Pandau Jaya Village is regulated in Kampar Regent's Regulation No. 32 of 2017 which was ratified on August 14, 2017. In the organization it was found that it was not in accordance with the process of the Village Head Election which was conducted in the first place by Pandau Jaya Village in 2017. Ie there were campaign conflicts when organizing the Pilkades campaign on November 13, 2017 until November 15, 2017 by each candidate for Pandau Jaya Village Head.            This study aims to examine the thesis of the road and the causes of conflict in the election of Village Head in 2017 in Pandau Jaya Village, Siak Hulu District, Kampar Regency. The theories used are conflict theory, political conflict theory, theory of conflict causes and conflict resolution theory. The research method used in writing this thesis is qualitative. The type of data in this study are primary data and secondary data. Data collection techniques in this study were interviews and documentation. The data analysis technique used is descriptive qualitative. The results of this study indicate that the conflict began during the campaign period, and there was a violation of the rules governing the pilkades carried out by the stronghold of the candidate for Pandau Jaya Village No. 3 Firdaus Roza namely entering the campaign area of the candidate for Village Head No. 2 Kamaluddin Siregar who later got protest from the camp No. 2 so there is conflict between the two camps. Keywords: Conflict Dynamics, Election of Pandau Jaya Village Head